Pemanfaatan Media Kartu Sebagai Media Pembelajaran Mengenal Huruf Anak Usia Dini - Ratna Azshari Suhana; Sima Mulyadi; Taopik Rahman (Journal on Education, 2024)
The use of learning media is very important in the teaching and learning process. The media used can make it easier for teachers to convey information to students, one of which is by using card media to introduce letters to young children. Card media is a simple media developed to create fun and interactive learning. Card media for introducing letters usually contains the letters A to Z along with picture words. Letter card media is one solution in improving the ability to recognize letters in early childhood. The method used in this research is the library study method or can be called literature study. The results of this research state that card media can be used to improve the ability to recognize letters in early childhood and can be used by teachers to facilitate learning in recognizing letters, making it easy to convey information related to letter recognition. The conclusion of this research is based on previous research articles related to the use of card media as a medium for learning to recognize letters. It suggests that card media can be used by teachers to facilitate the learning process and improve the ability to recognize letters in early childhood.